Effective AAV‐mediated gene therapy in a mouse model of ethylmalonic encephalopathy - Ivano Di Meo; Alberto Auricchio; Costanza Lamperti; Alberto Burlina; Carlo Viscomi; Massimo Zeviani (EMBO Molecular Medicine)
Abstract Ethylmalonic encephalopathy (EE) is an invariably fatal disease, characterized by the accumulation of hydrogen sulfide (H2S), a highly toxic compound. ETHE1, encoding sulfur dioxygenase (SDO), which takes part in the mitochondrial pathway that converts sulfide into harmless sulfate, is mutated in EE. The main source of H2S is the anaerobic bacterial flora of the colon, although in trace amount it is also produced by tissues, where it acts as a ‘gasotransmitter’. Here, we show that AAV2/8‐mediated, ETHE1‐gene transfer to the liver of a genetically, metabolically and clinically faithful EE mouse model resulted in full restoration of SDO activity, correction of plasma thiosulfate, a biomarker reflecting the accumulation of H2S, and spectacular clinical improvement. Most of treated animals were alive and well >6–8 months after birth, whereas untreated individuals live 26 ± 7 days. Our results provide proof of concept on the efficacy and safety of AAV2/8‐mediated livergene therapy for EE, and alike conditions caused by the accumulation of harmful compounds in body fluids and tissues, which can directly be transferred to the clinic.